2022
DOI: 10.3390/molecules27020514
|View full text |Cite
|
Sign up to set email alerts
|

Design and Evaluation of a Lactate Microbiosensor: Toward Multianalyte Monitoring of Neurometabolic Markers In Vivo in the Brain

Abstract: Direct in vivo measurements of neurometabolic markers in the brain with high spatio-temporal resolution, sensitivity, and selectivity is highly important to understand neurometabolism. Electrochemical biosensors based on microelectrodes are very attractive analytical tools for continuous monitoring of neurometabolic markers, such as lactate and glucose in the brain extracellular space at resting and following neuronal activation. Here, we assess the merits of a platinized carbon fiber microelectrode (CFM/Pt) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…The average biosensor sensitivity between 0.05 and 0.5 mM towards lactate was found to be 4.27 ± 1.35 nA mM −1 (n = 5). The results showed that the lactate microbiosensor exhibited comparable enzyme kinetics and analytical performance to previously described lactate microbiosensors [ 35 ].…”
Section: Resultsmentioning
confidence: 67%
“…The average biosensor sensitivity between 0.05 and 0.5 mM towards lactate was found to be 4.27 ± 1.35 nA mM −1 (n = 5). The results showed that the lactate microbiosensor exhibited comparable enzyme kinetics and analytical performance to previously described lactate microbiosensors [ 35 ].…”
Section: Resultsmentioning
confidence: 67%
“…The glucose concentration in bulk cerebrospinal fluid is approximately 4 mM, 52 whereas parenchymal glucose has been measured in the range of approximately 0.3–2.3 mM. 53 66 Accordingly, we wondered whether subtle changes in local glucose concentration through this physiological range would influence the degree of K ATP channel activity and modulate pericyte membrane potential (Vm). To permit direct monitoring of pericyte Vm, we isolated capillaries from Cspg4 -DsRed mice with intact thin-strand pericytes, and measured Vm using sharp microelectrode impalements ( Figure 4A ).…”
Section: Resultsmentioning
confidence: 99%